Live from Lincoln Center The Ashton Celebration in New York - Goldner, Nancy (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Ashton celebrated from New York. Once smitten with Isadora, always smitten. PALABRAS CLAVE: Frederick Ashton, Cinderella, Rhapsody, K-Ballet Company, Joffrey Ballet of Chicago, Birmingham Royal Ballet, Royal Ballet, Monotones, Enigma Variations, Dante Sonata, Les Patineurs, A Wedding Bouquet, The Two Pigeons, Five Brahms Waltzes in the Manner of Isadora Duncan.
Dentro del apartado "Celebrating Frederick Ashton. 17 September 1904 - 19 August 1988".